Strategic Impact of Shareholders ‘Say on pay’ on Executive Remuneration & Board Composition in UK - Saley, A (2013)
This research addresses two fundamental issues: first the strategic impact of shareholders votes on Executive pay (EP) and board compositions. The overall result from the analysis contends that say-on-pay votes have insignificant explanatory power on both remuneration and Board Composition (BC). Since the features of Executive Pay (EP) and BC are determined by both observable and unobservable firm characteristics. Both of which can only be determined by simultaneously looking at the endogenous (Size, Market Value (MV) or firm performance such as Return on Investment (RI), Dividends Yield (DY); as well as the exogenous (macroeconomic forces) characteristics and their relative impact on the performance of the firm. The empirical findings from this analysis show that shareholders involvement in pay determination as well as the composition and structures of corporate boards to improve the efficiency as well as the performance of the firms to certain degree. It also shows that activisms overall is one of the best and effective tools available to engage dispersed shareholders into the strategic decision making process; unlike the institutional shareholders whom can request to have close proximity representation on the board hence contributing directly to the strategic decisions made by board across the firm’s dimensions. The result shows an overall increase in firm value ex-post voting event. This is suggesting that firms who adapt say-on-pay could be seen in the coming future as potentially a secure source of investment. The study furthermore concludes by suggesting that even though say-on-pay is a viable monitoring tool, non-binding vote bring more strategic flexibility to the firm than biding shareholder votes. Because binding votes might steer the power of making important strategic decisions from the hand of the board of directors whom are better placed to do so into the hand of perhaps immature or self-interest driven shareholders. The study furthermore support that more research is required in the field of say-on-pay due to the lack of consistency in findings from previous literature.